Sala de aula invertida: uma proposta de modelo híbrido para aprendizagem em estatística no ensino médio integrado - Almeida, Jacqueline Oliveira de (2023)
This research aims to analyze the Flipped Classroom methodology mediated by TDIC in the Teaching of Applied Statistics in a 2nd grade class of Integrated High School at the Federal Institute of Education, Sciences and Technology of Sergipe — IFS. The need for this study emerges from society's growing interest in the use of Blended Learning, which was intensified with the pandemic period and due to the dynamics and needs of generation Z, which requires easy access to information that can be provided by TDIC. In this sense, we started with some research questions: How is the methodology of the Flipped Classroom mediated by DICT processed? How is the satisfaction and performance of students in relation to this methodology? And, what is the teacher-student and student-student relationship from the perspective of this methodology? To answer these questions, this study followed the principles of a qualiquantitative approach, whose adopted procedures were based on the “Action Research” method from Thiollent (1986). Following some fundamental steps such as: planning, implementation, and production of data to investigate the performance and satisfaction of everyone involved in this experience. Having as theoretical assumptions for the analysis of this study: Bergmann and Sams (2018), Valente (2018), Correia, E. et al. (2020), Lombard (2003) and Faerber (2003). Based on the theory, one can observe the development and learning of students with the use of the methodology under study through the activities that took place in the online and face-toface moments, highlighted by the importance of the teacher-student and student-student relationship potentiated by what TDIC offer for learning, which are established through mediation and cooperation between the subjects during the application of the SAI, these endowed with their own desires and meanings, linked by various identity, epistemic and social issues, in the search for knowledge through teaching and learning. In addition, student satisfaction with the application of the SAI methodology in the discipline of Applied Statistics was identified, leading to a much more attractive and meaningful learning.